College Readiness and College Completion at Broad Access Four-Year Institutions. (July 2014) - Jackson, Jacob; Kurlaender, Michal
Many students arrive at college unprepared to do college-level work, facing a host of college readiness assessments and developmental education coursework. In this article, we examine how a student's readiness to take college classes upon entry to the university is related to four longer term postsecondary outcomes. We utilize a unique longitudinal dataset of the census of first-time freshmen at the nation's largest public 4-year state postsecondary system to describe differences by campus and across college majors. In addition we explore the use of one measure that the system does not currently use to determine readiness—high school grade point average—and its relationship with both the existing readiness measure and postsecondary outcomes. Our results indicate that grade point average can be a useful predictor of college success above and beyond the readiness measure.